Improving Production Quality in the Blow Molding Process for 600ml Bottles Using the Taguchi Method - Zico Alchory Yarangga; Miftachul Huda (International Journal of Health Engineering and Technology, 2025)
This study addresses the challenge of optimizing the blow molding process for producing 600ml PET bottles, which is critical to ensuring consistent product quality and manufacturing efficiency amid increasing industry demands. The primary objective is to identify the optimal process parameters—air pressure, heating temperature, and stretching time—that minimize defect rates. Employing a quantitative experimental approach, the research utilizes the Taguchi method with an orthogonal array L9 (3³) design to systematically investigate the effects of these parameters. The population comprises PET bottles produced under varying process conditions at a manufacturing facility, with a sample size of 1,260 bottles across nine experimental treatments. Data collection involved defect counting and quality inspection, analyzed through Signal-to-Noise Ratio (SNR), Analysis of Mean (ANOM), and Analysis of Variance (ANOVA) techniques using specialized software. The results reveal that the optimal parameters are an air pressure of 33 bar, a heating temperature of 150°C, and a stretching time of 0.933 seconds, with air pressure being the most influential factor. The findings suggest that precise control of these parameters significantly reduces defects, enhances process stability, and improves product quality. However, limitations include the specific industrial setting and focus solely on defect count. Future research should explore additional quality metrics and broader process variables to further optimize blow molding processes for various bottle sizes and materials.